Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1637/7286-100404r
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bacteriophages in Combination with Competitive Exclusion to Reduce Salmonella from Infected Chickens

Abstract: Salmonella-spedfic bacteriophages (BP) and competitive exclusion (CE) were used to reduce Salmonella colonization in experimentally infected chickens. A "cocktail" of distinct phage (i.e., phage showing different host ranges and inducing different types of plaques on Salmonella Typhimurium [ST] cultures) was developed. The killing activity of the selected BPs on ST cultures differed significantly, as determined in in vitro killing assays. BPs were administered orally to the chickens several days prior and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 22 publications
3
71
2
2
Order By: Relevance
“…Moreover, there was a marginally improved weight gain in the treated animals. Although both approaches were able to reduce the Salmonella counts, unlike the previous study (Borie et al, 2009) a synergistic effect was not observed (Toro et al, 2005).…”
Section: Salmonellacontrasting
confidence: 73%
See 1 more Smart Citation
“…Moreover, there was a marginally improved weight gain in the treated animals. Although both approaches were able to reduce the Salmonella counts, unlike the previous study (Borie et al, 2009) a synergistic effect was not observed (Toro et al, 2005).…”
Section: Salmonellacontrasting
confidence: 73%
“…Moreover, they showed that phage treatment coupled with competitive exclusion resulted in even better Salmonella r e d u c t i o n s t h a n e a c h o f t h e treatments alone (Borie et al, 2009). Toro et al (2005) and coworkers also tested the association of phage therapy and competitive exclusion in the treatment of chickens infected experimentally with Salmonella. Phage treatment was given orally and included a cocktail of three different phages with different host ranges.…”
Section: Salmonellamentioning
confidence: 99%
“…Phage therapy has shown promise as an effective pre-harvest intervention by controlling foodborne pathogens in animals before they enter processing plants, [2][3][4] with several studies indicating that phage therapy is effective against a broad range of foodborne pathogens belonging to the genera Salmonella, Campylobacter, Listeria and Escherichia. [5][6][7][8][9] Phage therapy has been investigated for efficacy in red meat producing animals (cattle, sheep, swine) and white meat producing animals (poultry).…”
Section: Pre-harvest Control Of Foodborne Pathogens In Food Producingmentioning
confidence: 99%
“…[2][3][4]10 Generally, the use of only one phage in some experiments has led to resistance, 2,10 while the use of multiple phages in a cocktail has decreased the chance of developing resistance to a single phage. 4,7,11 Ruminants. Phage based interventions have been aimed at controlling Escherichia coli (E. coli) serotype O157:H7 in cattle and other ruminants.…”
Section: Pre-harvest Control Of Foodborne Pathogens In Food Producingmentioning
confidence: 99%
See 1 more Smart Citation